Growth response of not-ready-to-distribute tea (Camellia sinensis (L) o. Kuntze) seedlings due to application of biofertilizer at various concentrations and intervals - Anjarsari, Intan Ratna Dewi; Rosniawaty, Santi; Panggabeaan, Johannes Yesse (Universitas Padjadjaran, 2023)
The plantation rejuvenation program makes the need for ready-to-distribute tea seedlings getting higher. Meanwhile, the nursery's seedlings are mostly not ready to distribute. This study aimed to determine the response of not-ready-distribute tea seedlings due to the application of biofertilizers at various concentrations and intervals. This experiment was carried out at Gambung Tea and Quinine Research Center Nursery, conducted from December 2021 to February 2022 at an altitude of 1,350 meters above sea level (asl). The experimental method used was a randomized block design with eight treatment combinations, namely: control (no fertilizer); urea fertilizer every two weeks; Biofertilizer 5 mL L-1 + interval once a week; Biofertilizer 5 mL L-1 + interval every two weeks; Biofertilizer 10 mL L-1 + break once a week; Biofertilizer 10 mL L-1 + interval every two weeks; Biofertilizer 15 mL L-1 + interval once a week; Biofertilizer 15 mL L-1 + interval every two weeks, all repeated four times. The experimental results showed that treatment of biological fertilizers influenced the parameter number of leaves and chlorophyll index. The application of biofertilizer with a concentration of 15 mL L-1 + interval of 2 weeks greatly influenced the parameters of leaf number and chlorophyll content index.